Legal Review of the Criminal Act of Rolling Football Gambling in Golewa District - Pare, Prisko Yanuarius Djawaria; Tanggo, Maria Dorti; Ine, Maria Yasinta; Tea, Margaretha; Repu, Maria Theresia (PT FORMOSA CENDEKIA GLOBAL, 2024)
The phenomenon of gambling is considered normal by some people, in fact this act takes root and develops just like that, if there is no action taken by law enforcement it will certainly become a disease that will then destroy life. Gambling often involves children, young people, including the elderly, this condition will trigger disorganization and disintegration in community life. Author in tackling criminal acts of gambling. The research method is in the form of legal-empirical research which examines and examines real law. The data used is from mass media literature such as results from television, cellphones, journals, books, previous research and official documents. The results of the research findings show, First, criminal acts in the form of rolling ball gambling both when there are single organ events at night and during the day. Second, a strategy for dealing with criminal acts of gambling by conducting outreach, preventive and repressive efforts. The crime of rolling ball gambling is widespread at night, and also on market days in Golewa sub-district, specifically located at the Malanuza people's market. Many football bookies play this action and attract a lot of attention, from teenagers to the elderly. A lot of money is scattered when the ball has traveled on the roll ball board, and the players enter the numbers chosen with the betting money.